Genotype × Environment Interaction and Stability Analysis for Grain Yield of Mid-hill Rice Genotypes - Upreti, Hari K.; Bista, Sudarshan; Sah, Surya N.; Dhakal, Ramesh (Nepal Agriculture Research Journal, 2014)
Genotype x Environment interaction limits the effectiveness of selection when selection is based only on mean yield. This G × E interaction was studied for grain yield in 7 genotypes of mid-hill rice in five different environments across the Nepal. Significant difference was observed among genotype (G), environment (E) and interaction (G × E) but could not identify the stable high yielding genotypes for diverse environments. Therefore, stability parameters were calculated and analyzed. On the basis of stability parameters, two genotypes, NR 10414, NR 10492 and NR 10515 were found to be most stable over different environments. NR 10353 was identified as suitable genotypes with high grain yield for favorable environment. Nepal Agric. Res. J. Vol. 8, 2007, pp. 14-17 DOI: http://dx.doi.org/10.3126/narj.v8i0.11565